2014
DOI: 10.1007/s12017-014-8309-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Signatures and Their Correlation with Clinicopathological Features in Glioblastoma Multiforme

Abstract: The increasing interest in identifying molecular biomarkers to determine patient prognosis in glioblastoma multiforme (GBM) has resulted in several microRNA (miRNA)-based signatures able to predict progression-free and overall survival. However, the coherency between these signatures is small, and correlations to clinicopathological features other than survival are seldom seen. The aim of this study was to identify any significant relationship between miRNA signatures and clinicopathological data by combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…These multi-vesicular endosomes are typically destined for recycling by lysosomes, but occasionally fuse with the plasma membrane and thereby release their microvesicle contents into the extracellular milieu. Exosomes contain a representative profile of the proteins, mRNAs, and microRNAs of their parent T-cells; in glioblastoma (GBM) this exosomal content reflects the tumor's unique signature of EGFR amplification, EGFRvIII mutation, IDH1 mutation R132H, TGF-β, and/or podoplanin status (Al-Nedawi et al, 2008;Graner et al, 2009;Henriksen et al, 2014;Li et al, 2013;Manterola et al, 2014;Noerholm et al, 2012;Shao et al, 2012). GBM-derived exosomes also may beckon angiogenesis during hypoxia, by delivery of proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These multi-vesicular endosomes are typically destined for recycling by lysosomes, but occasionally fuse with the plasma membrane and thereby release their microvesicle contents into the extracellular milieu. Exosomes contain a representative profile of the proteins, mRNAs, and microRNAs of their parent T-cells; in glioblastoma (GBM) this exosomal content reflects the tumor's unique signature of EGFR amplification, EGFRvIII mutation, IDH1 mutation R132H, TGF-β, and/or podoplanin status (Al-Nedawi et al, 2008;Graner et al, 2009;Henriksen et al, 2014;Li et al, 2013;Manterola et al, 2014;Noerholm et al, 2012;Shao et al, 2012). GBM-derived exosomes also may beckon angiogenesis during hypoxia, by delivery of proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have found hsa-miR-19b-3p that has been reported to be upregulated in serum of children with autism [67]; in fact, hsa-miR-19b-3p has been suggested as a possible candidate for circulating miRNA-based prediction-marker of autism. Among other miRNA's of interest here, hsa-miR-5585-5p was found to be associated with glioblastoma [68], hsa-miR-5095 and hsa-miR-1273a were detected in microvesicles released from glioma cells [69] and hsa-miR-136-5p was reported as associated with Alzheimer's disease [70].…”
Section: Genetics Of Human Eaats; Possible Involvement In Diseasementioning
confidence: 81%
“…C, Effect of glucose deprivation on miR-9 expression in 9 L cells plated at 5000, 50,000, or 250,000 cells/cm suggests coordinated regulation of the switch. Most miRNAs simultaneously regulate multiple targets, thereby conducting multifaceted changes in protein expression [5,49,50]. Several miRNAs have been identified that correlate to clinical outcomes and modulate glioblastoma proliferation and invasion [9,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Most miRNAs simultaneously regulate multiple targets, thereby conducting multifaceted changes in protein expression [5,49,50]. Several miRNAs have been identified that correlate to clinical outcomes and modulate glioblastoma proliferation and invasion [9,[50][51][52]. In an effort to elucidate the signaling mechanisms that regulate the switch from proliferation to invasion in malignant glioma, we performed LCMD to isolate glioma cells from the primary tumor and from invasive tumor islets located >100 μm from the tumor boundary.…”
Section: Discussionmentioning
confidence: 99%